2014
DOI: 10.1136/bjophthalmol-2013-304615
|View full text |Cite
|
Sign up to set email alerts
|

Cone photoreceptor definition on adaptive optics retinal imaging

Abstract: AimsTo quantitatively analyse cone photoreceptor matrices on images captured on an adaptive optics (AO) camera and assess their correlation to well-established parameters in the retinal histology literature.MethodsHigh resolution retinal images were acquired from 10 healthy subjects, aged 20–35 years old, using an AO camera (rtx1, Imagine Eyes, France). Left eye images were captured at 5° of retinal eccentricity, temporal to the fovea for consistency. In three subjects, images were also acquired at 0, 2, 3, 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 28 publications
6
54
0
Order By: Relevance
“…2935,49 Yet only 2 studies using AOSLO to date reported cone density or center-to-center spacing in the very foveal center, and both assessed fewer than 5 eyes. 31,36 Large inter-subject variability of foveal cones was shown by Li and co-workers who analyzed foveal centers in 4 eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2935,49 Yet only 2 studies using AOSLO to date reported cone density or center-to-center spacing in the very foveal center, and both assessed fewer than 5 eyes. 31,36 Large inter-subject variability of foveal cones was shown by Li and co-workers who analyzed foveal centers in 4 eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advance in adaptive optics (AO) assisted retinal imaging 2128 has made it possible to assess in the living human eye cone density, 2935 which could be characterized previously only by histology. Although AO retinal imaging offers significant advantages in studying the impact of chorioretinal diseases on cones, the density and the variability of the foveal cones, especially cones in the very foveal center, have not been adequately assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The two eccentricities were chosen to be a compromise between the resolution limit of the instrument, which does not allow cones to be resolved too close to the fovea (i.e. closer than 1 degree), and the presence of rods, which alter the cone relative spacing enough to be detectable by the rtx1 when further than 5 degrees [32]. The time between the images ranged from 45 minutes to 3 years at 2.5 degrees and from 45 minutes to 4 months at 4.0 degrees.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Foveal cone tips are not visible on the rtx1 device because the resolution of the system is only 250 line pairs per mm. Therefore, cone identification within 2.5° from the foveal center is unreliable and not suitable for quantification [36]. …”
Section: Methodsmentioning
confidence: 99%